2017
DOI: 10.1186/s40608-016-0139-8
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index–measured adiposity and population attributability of associated factors: a population-based study from Buea, Cameroon

Abstract: BackgroundObesity is currently a global health challenge driven by a mix of behavioural, environmental and genetic factors. Up to date population-based disease burden estimates are needed to guide successful prevention and control efforts in African countries. We investigated the prevalence and population attributable fractions of overweight and obesity in Buea, the Southwest region of Cameroon.MethodsData are from a community-based cross-sectional study involving randomly selected adults conducted in 2016. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 38 publications
7
33
2
Order By: Relevance
“…Full texts of the remaining 76 records were scrutinized for eligibility, among which 50 were excluded. In the end, 26 studies were retained for meta‐analysis (Supporting Information Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full texts of the remaining 76 records were scrutinized for eligibility, among which 50 were excluded. In the end, 26 studies were retained for meta‐analysis (Supporting Information Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies were conducted in an urban area only, two in a rural area only, and seven in both urban and rural areas (Supporting Information Table S4). Twenty‐four studies measured BMI , sixteen measured WC , eight measured WHR , and two measured %BF .…”
Section: Resultsmentioning
confidence: 99%
“…Another study has shown that the dependency between socio-economic status and obesity depends on population, gender and age 30 . In Ethiopia the prevalence of overweight and obesity were 14.7 and 5.8%, respectively 31 . Girls (16.5%) were more overweight than boys (12.3%), nevertheless males (8.6%) were more obese than female children (3.8%).…”
Section: Discussionmentioning
confidence: 99%
“…These observations are occurring in a country with poor CVD risk profiles; around one in 4 individuals with raised blood pressure [39], about a third being overweight or obese [40], and increasing rates of stroke and stroke mortality [36] in Cameroon.…”
Section: Discussionmentioning
confidence: 99%